CHILD SEXUALITY: RELATIONSHIP BETWEEN SEX EDUCATION AND GENDER IDENTITY - Celli de Oliveira, Maria Fernanda [UNESP]; Muzzeti, Luci Regina [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
We know that issues related to sexuality are intrinsically linked to the integral development of any individual. Considering that even today it is common to find resistance in relation to the theme, especially at school, where most of the educators feel uncomfortable or not able to deal with such issues, we intend, with this work, to raise some thoughts about the possible intertwining between sex education and the structuring of gender identity regarding children in early childhood education, based on Pierre Bourdieu's assumptions. Based on the analysis of the cultural heritage (a concept developed by the aforementioned sociologist) of three school agents, we seek to problematize in this work some discussions about the interference of this heritage regarding the sexual education provided to children in the scope of early childhood education, causing a reflection based on importance of sex education inside and outside the school environment.
Keywords: Child education; Sex education; Gender identity; Child sexuality